Students’ Perceptions of the Use of English at a Bilingual Setting Based on Their Kindergarten Language Background - Surdyanto, Annas (University of Muhammadiyah Prof. DR. HAMKA, 2016)
This research investigated what students with English-kindergarten, Indonesian-kindergarten, and English-Indonesian-kindergarten background perceived regarding the use of English at a bilingual school. The study adopted a qualitative case design and took place at one of private primary schools in Jakarta. There were 27 participants (14 males and 13 females) being involved in this research. They were 21 students of grade one, 3 students of grade two, and 3 students of grade three. Most students with English-kindergarten background gave positive perceptions of the use of English, while most students with Indonesian-kindergarten background had negative perceptions of the use of English. Students with bilingual kindergarten background gave positive perceptions of the use of English at bilingual school. The findings can show that there is a correlation between students’ previous exposure to a foreign language and their future preference for the language used as the medium of teaching-learning processes. This study can contribute to the policy making of schools which intend to adopt bilingual education.